Factors associated with the self-efficacy of private practice general practitioners in the diagnosis and management of mental disorders in Bali, Indonesia - Wirajaya, I Komang; Sri Nopiyani, Ni Made; Jaya Lesmana, Cok Bagus (Public Health and Preventive Medicine Archive, 2025)
Background and purpose: General practitioners’ self-efficacy plays a crucial role in the successful diagnosis and management of mental disorders in primary care settings. In Bali, there is limited data on the factors influencing the self-efficacy of private practice general practitioners in handling mental health disorders. This study aimed to identify the factors associated with the self-efficacy of private practice general practitioners in the diagnosis and management of mental disorders in Bali. Methods: This was an analytical cross-sectional study involving 109 private practice general practitioners in Bali, conducted from September 2024 to March 2025. The sample included general practitioners who possessed a valid practice license, practicing either independently or at primary clinics in four cities/districts, selected using convenience sampling. Self-efficacy in this study was measured with the adapted General Self-Efficacy Scale (GSE). Data were collected through a structured self-administered questionnaire, which covered demographic characteristics, direct experience, vicarious experience, social persuasion, and emotional-physiological states. Data analysis was performed using Chi-square tests and multiple logistic regression. Results: The results showed that 67.0% of respondents had low self-efficacy in diagnosing and managing mental disorders. Factors significantly associated with self-efficacy among private practice general practitioners included direct experience (aOR=4.39; 95%CI: 1.59–12.10; p=0.004), social persuasion (aOR=3.58; 95%CI: 1.36–9.46; p=0.010), and emotional-physiological state (aOR=2.90; 95%CI: 1.14–7.42; p=0.025). Meanwhile, age, gender, years of practice, and vicarious experience were not significantly associated with self-efficacy. Conclusion: Direct experience, social persuasion, and emotional-physiological states were found to be factors associated with the self-efficacy of private practice general practitioners in diagnosing and managing mental disorders. It is recommended that the government develop